Roles of FGFs as Adipokines in Adipose Tissue Development, Remodeling, and Metabolism - Itoh, Nobuyuki; Ohta, Hiroya (Frontiers in Endocrinology, 2014)
White and brown adipose tissues, which store and burn lipids, respectively, play critical roles in energy homeostasis. Fibroblast growth factors (FGFs) are signaling proteins with diverse functions in development, metabolism, and neural function. Among twenty-two FGFs, FGF1, FGF10, and FGF21 play roles as adipokines, adipocyte-secreted proteins, in the development and function of white and brown adipose tissues. FGF1 is a critical transducer in white adipose tissue remodeling. The PPARγ–FGF1 axis is critical for energy homeostasis. FGF10 is essential for embryonic white adipocyte development. FGF21 activates brown adipose tissue in response to cold exposure. FGF21 also stimulates the accumulation of brown-like cells in white adipose tissue during cold exposure and is an upstream effector of adiponectin, which controls systemic energy metabolism. These findings provide new insights into the roles of FGF signaling in white and brown adipose tissues and potential therapeutic strategies for metabolic disorders.